2002
DOI: 10.1136/bmj.325.7365.628
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of long term effects of advice to reduce dietary salt in adults

Abstract: Objective To assess the long term effects of advice to restrict dietary sodium in adults with and without hypertension. Design Systematic review and meta-analysis of randomised controlled trials. Data sources Cochrane library, Medline, Embase, and bibliographies. Study selection Unconfounded randomised trials that aimed to reduce sodium intake in healthy adults over at least 6 months. Inclusion decisions, validity and data extraction were duplicated. Random effects meta-analysis, subgrouping, sensitivity analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
169
1
11

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(185 citation statements)
references
References 41 publications
4
169
1
11
Order By: Relevance
“…Smaller effects of sodium reduction on DBP than SBP are reported frequently from clinical trials of sodium reduction [2][3][4][5]28 with the apparent, although usually implicit, assumption that the expected effect on SBP and DBP is of the same importance, even if not in magnitude. However, this view is contrary to an increasing body of literature both from large cohort studies, especially the approximately 350 000 middle-aged men screened for the Multiple Risk Factor Intervention Trial 29 and from randomized trials focused on systolic hypertension in older persons.…”
Section: Systolic Vs Diastolic Blood Pressurementioning
confidence: 99%
See 2 more Smart Citations
“…Smaller effects of sodium reduction on DBP than SBP are reported frequently from clinical trials of sodium reduction [2][3][4][5]28 with the apparent, although usually implicit, assumption that the expected effect on SBP and DBP is of the same importance, even if not in magnitude. However, this view is contrary to an increasing body of literature both from large cohort studies, especially the approximately 350 000 middle-aged men screened for the Multiple Risk Factor Intervention Trial 29 and from randomized trials focused on systolic hypertension in older persons.…”
Section: Systolic Vs Diastolic Blood Pressurementioning
confidence: 99%
“…The level of sodium reduction in TOHP II approximates the maximum that can be achieved and maintained by individuals making food selections in the community even when these individuals are highly motivated and extensively counseled. 4,5,[34][35][36] Even the relatively modest level of sodium reduction observed in TOHP II is unlikely to be attained in the general US population without changes in the food supply.…”
Section: Public Health Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the evidence is not without contention and results from meta-analyses have been mixed (5)(6)(7) . Graudal et al concluded in 1998 that studies did not support a general recommendation to reduce Na intake but did support use as a supplementary treatment in hypertension (8) .…”
mentioning
confidence: 99%
“…This supports the Cochrane Collaboration conclusion that there was not sufficient evidence for a general dietary recommendation to reduce sodium intake. 11 Parenthetically, it is interesting to note that in countries where most sodium intake is discretionary, as parts of East Asia, sodium intake is much higher than in Britain, where most sodium is not discretionary, but consumed in our foods! The restricted focus of this report does not detract from the careful analysis and lucid presentation by He et al 5 It does, however, account for my dissent from the call for British youngsters to reduce their sodium intake.…”
mentioning
confidence: 99%